'MISTAKES' IN TRANSLATION: A FUNCTIONALIST APPROACH - Harry Aveling (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
Translators are regularly berated by various criticsfor their apparently endless "mistakes ". All of us who are practising translators know this well. We labour for years to trails late a text, ill a sensitive and caring way, only to be told that "there is a comma missing on page 45 ", "this sort of bird is a pigeoll alld not a magpie ", and "the subjunctive, which is a particular feature of this author s style in the original, is missing in the translation". Mistakes, mistakes, mistakes. In choosing this particular topic, I have the sense that it is one for which my critics, at least, consider me singularly qualified. In this article, I wish to consider here whether it is still meaningful to consider "mistakes" as a failure to achieve" equivalence, adequacy, accuracy, etc., " especially in these postmodern days in which the concept of multiple readings is well established. Part of my argument will also distinguish between what might be initially considered "dumb mistakes" (foolish errors) and "deliberate mistakes", the latter occurring when a translator specifically chooses to recreate the text in a way that seems to deviate from the literal surface meaning of the source text. Thirdly, I will suggest that the evaluation of translation needs not to insist that" This is wrong ", but rather to ask" Why has the translator chosen this particular way of translation?" and" What is it that s/he is trying to bring across from the original text into the re-enactment of it?"